Implementasi Google Family Link Sebagai Solusi Pengawasan Penggunaan Gadget Anak di Desa Sundamekar - Rospita, Sonia; Firmansyah, Esa; Helmiawan, Muhammad Agreindra (Yayasan Pendidikan Tanggui Baimbaian, 2024)
Abstract This study aims to explore the implementation of Google Family Linkas a solution for supervising children's gadget usage in Sundamekar Village. With the growing use of gadgets among children, especially with the advancements in technology, parents face challenges in managing both the time and content accessed by their children. By applying the Google Family Link application, this study examines its effectiveness in helping parents monitor and limit gadget usage. The methods used include socialization sessions for parents regarding the application's features and training on its use. The results show a significant increase in parents' knowledge of digital supervision and a reduction in children's gadget usage duration. These findings indicate that Google Family Link can be an effective tool to support parents in creating a healthier digital environment for children in Sundamekar Village. This study is expected to contribute to the development of improved digital supervision policies in the community.